Sports Performance Analysis of Canoeing Athletes: Is there a Difference between Sprint and Slalom Canoeing? - Kocahan, Tuğba; Akınoğlu, Bihter; Kabak, Banu; Deliceoğlu, Gökhan; Tortu, Erkan; Hasanoğlu, Adnan (Spor Hekimligi Dergisi/Turkish Journal of Sports Medicine, 2020)
Objective: The purpose of this study was to investigate the respiratory function, respiratory muscle strength, postural sway and aerobic capacity parameters of canoeing athletes, and to compare these parameters between sprint and slalom canoeing athletes. Materials and Methods: A total of 34 male canoeing athletes that are composed of 15 sprint and 19 slalom canoeing athletes, with an average age of 20.4±1.6 years, were included in the study. Respiratory function and respiratory muscle strength of the athletes were measured with a digital spirometer, postural sway was measured with the Body Sway Module, and aerobic capacity was measured using a breath-by-breath automatic portable gas analysis system. Independent samples T-test was used to compare the variables obtained from sprint and slalom canoeing athletes. Statistical error level was taken as p<0.05. Results: It was determined that there were no statistically significant differences between the respiratory function, inspiratory and expiratory respiratory muscle strength, postural sway and aerobic capacity parameters of sprint and slalom canoeing athletes (p>0.05). Conclusion: The results obtained from this study reveal that sprint and slalom canoeing athletes have similar respiratory function, respiratory muscle strength, postural sway and aerobic capacity. These results can be used as an initial reference to define training program requirements to increase peripheral muscle strength, respiratory function, respiratory muscle strength, postüral sway, and aerobic capacity in canoeing athletes.